Pengaruh Pendekatan Saintifik Melalui Model PBL Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Fikih Kelas XI IPA di MAN 1 Pasaman Barat - Dewita, Resma; C, Charles; A, Afrinaldi; Dewi, Yelfi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The inadequate critical thinking skills of children in education spurred this study. Therefore, a scientific method is one of the learning strategies required to help pupils to acquire their critical thinking abilities. One learning model capable of supporting a scientific approach is the PBL model. This study thus seeks to determine the extent of effect the